ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA MELALUI PENERAPAN STRATEGI SCAFFOLDING - Susanti susanti; Zainal Abidin; Rina Mauliza (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2021)
This descriptive qualitative research aims to describe the mathematical representation abilities of students through the application of the scaffolding strategy. The subjects of this study were 2 students with low representation abilities and 2 students with moderate representation abilities in class VIII-4 of SMP Negeri 6 Banda Aceh. The data was collected by means of a mathematical representation ability test sheet, interviews, and a recording device. Then data analysis by reducing data, presenting data, triangulating time, and drawing conclusions. The results showed that subjects with low representation skills tended to perform visual representations, but after scaffolding they were able to use visual representations independently and verbal representations by checking several times. Meanwhile, subjects with moderate representation ability tend to perform visual and verbal representations with multiple checks and symbolic representations with several interventions, after scaffolding they are able to use visual and verbal representations independently, even though symbolic representations still require several interventions. This shows that the students' representation ability gets better after being given a scaffolding strategy.